Food-Associated Stress Primes Foodborne Pathogens for the Gastrointestinal Phase of Infection - Horn, Nathan; Bhunia, Arun K. (Frontiers in Microbiology, 2018)
The incidence of foodborne outbreaks and product recalls is on the rise. The ability of the pathogen to adapt and survive under stressful environments of food processing and the host gastrointestinal tract may contribute to increasing foodborne illnesses. In the host, multiple factors such as bacteriolytic enzymes, acidic pH, bile, resident microflora, antimicrobial peptides, and innate and adaptive immune responses are essential in eliminating pathogens. Likewise, food processing and preservation techniques are employed to eliminate or reduce human pathogens load in food. However, sub-lethal processing or preservation treatments may evoke bacterial coping mechanisms that alter gene expression, specifically and broadly, resulting in resistance to the bactericidal insults. Furthermore, environmentally cued changes in gene expression can lead to changes in bacterial adhesion, colonization, invasion, and toxin production that contribute to pathogen virulence. The shared microenvironment between the food preservation techniques and the host gastrointestinal tract drives microbes to adapt to the stressful environment, resulting in enhanced virulence and infectivity during a foodborne illness episode.